Implementation of Local Wisdom Values of Acehnese Regional Language for Character Building of Students in Improving the Quality of Education in State Junior High Schools of Samatiga District - Marlina Dahlan; Rahmattullah Rahmattullah; Musdiani Musdiani (Dinasti Publisher, 2025)
A study is needed at Samatiga District State Junior High School to investigate how applying local Acehnese wisdom values in learning can improve student character and educational quality. Current learning often neglects these values, focusing mainly on cognitive and skill aspects, leaving negative student behaviors unaddressed. This qualitative study aims to describe and analyze the application of Acehnese local wisdom in shaping the character of seventh-grade students and enhancing education quality. Data will be collected through interviews, observations, and documentation from the principal and teachers, and analyzed descriptively. Initial findings suggest that using Acehnese local wisdom fosters discipline, polite communication, patriotism, respect for local customs, and adherence to school rules. Furthermore, it appears to improve learning quality by making material easier to understand, serving as an effective learning introduction, and providing relevant real-world examples.